Cultivo in vitro de embriões de coquinho azedo (Butia capitata (Mart.) Becc) - Carneiro, Pedro Augusto Porto (2012)
The experiments were conducted in Uberlândia, Minas Gerais and the fruits of Butia capitata (Mart) Becc were collected in the region of Montes Claros - MG. Different embryo immersion times were tested in the first experiment, using 0.25% chlorine solution for 10, 20 or 30 minutes, and immersed, or not, for 10 minutes in a solution of the fungicide methyl thiophanate at 1.5 mL L-1. There was no need for the use of fungicide for contamination control, and treatment with 0.25 % chlorine solution for 10 to 30 minutes was sufficient. The second experiment was done in a completely randomized design with 8 treatments, 4 replicates and 12 plots. Treatments consisted of the addition of different antioxidants (control - absence of antioxidants; ascorbic acid - 100 mg L-1; PVP - 400 mg L-1 and activated charcoal - 3.0 g L-1) to the MS medium with 75% ionic strength, with or without immersion in ascorbic acid solution (100 mg L-1). The following characteristics were evaluated after 45 days: oxidation (in %), observed as darkening of the embryo structures; germination (in %) and normal plants ( % ), considering as normal plants those emitting both shoot and rootlet, while for germination the presence of any of these parts was counted. The last experiment was done as a 4x4 factorial in a completely randomized design with 16 treatments, 3 replicates and 2 plots. The treatments were characterized by the combination of 4 doses of BAP (0, 0.96, 1.92 or 3.84 mg L-1), and 4 doses of ANA (0, 0.24, 0.48 or 0.96 mg L-1), added to the MS medium with 75% of ionic strength. The following characteristics were evaluated after 110 days: number of leaves; leaf main length (cm), length of the main root; shoot and root dry matter. There was no significant interaction between the measurements of ANA and BAP for any of characteristics evaluated. Greater leaf length was obtained using 0.47 mg L-1 of ANA.